2020
DOI: 10.1038/s41598-020-70528-7
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between airway and gut microbiome links to IgE responses to house dust mites in childhood airway allergies

Abstract: A connection between airway and gut microbiota related to allergen exposure in childhood allergies was not well addressed. We aimed to identify the microbiota alterations in the airway and gut related to mite-specific IgE responses in young children with airway allergies. This study enrolled 60 children, including 38 mite-sensitized children (20 rhinitis and 18 asthma), and 22 non-mite-sensitized healthy controls. Microbiome composition analysis of the throat swab and stool samples was performed using bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…Counterintuitively, all of the statistically significant OM-85-induced differences we observed occurred in PVG rats, although the biological relevance of these changes is uncertain, given the median magnitude of change was roughly half a percent (or less) in terms of relative abundance. Furthermore, other genera were not affected by OM-85 pretreatment: Dorea remained under-represented in T2hi BN rats both pre-and post-OM-85, consistent with other reports of reduced Dorea in stools of children with mite-sensitised rhinitis (68), and young adults with food allergy and sensitisation (69). Our observation that orally administered OM-85 had significant effects on the lung compartment in asthma-susceptible BN rats does suggest that interactions between the gut and lung contribute to disease expression and resolution.…”
Section: Discussionsupporting
confidence: 90%
“…Counterintuitively, all of the statistically significant OM-85-induced differences we observed occurred in PVG rats, although the biological relevance of these changes is uncertain, given the median magnitude of change was roughly half a percent (or less) in terms of relative abundance. Furthermore, other genera were not affected by OM-85 pretreatment: Dorea remained under-represented in T2hi BN rats both pre-and post-OM-85, consistent with other reports of reduced Dorea in stools of children with mite-sensitised rhinitis (68), and young adults with food allergy and sensitisation (69). Our observation that orally administered OM-85 had significant effects on the lung compartment in asthma-susceptible BN rats does suggest that interactions between the gut and lung contribute to disease expression and resolution.…”
Section: Discussionsupporting
confidence: 90%
“…On the one hand, it has been demonstrated that a modulation of HDM exposure (which elevated immunoglobulin E level) in case of microbial dysbiosis can change the gut microbial community (65). In addition, IgE is also produced locally in the gut; the particular subsets of airway microbiome dysbiosis-associated HDM-specific IgE response can interact with corresponding gut microbiome by changing the IgE levels in the gut through the gut-lung axis (65,66). On the other hand, the gut microbiome affects the levels of serum IgE depending on metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal relative abundance of Escherichia was higher in children with asthma or rhinitis than in controls 52 . The positive association between Escherichia and asthma was replicated in another study 53 . In infants, a high abundance of E. coli was associated with an increased risk of atopic eczema 54 .…”
Section: Principal Dietary Sources Of Vitamin a Were Retinol From Animal Foods And Provitaminmentioning
confidence: 67%